(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
Interview Time: February 12, 2015, at 4PM -10PM. Interview Venue: Tan Zhiyuan’s home. Interviewed by Wang Xiaoxin (hereinafter, WANG), lecturer of Shanghai Theatre Academy Puppet Program, M.A. of Peking University, Special Research Fellow of Yale University Drama School. Interview to Tan Zhiyuan (hereinafter, TAN), Former Vice Chair of the China National Puppet Arts Troupe, First-grade Puppeteer, Member of Chinese Dramatists Association, Member of Council of China Puppetry and Shadow Arts Association. Rod puppet is an important form of Chinese puppet. Its structure and performing techniques are quite different from that of marionette and hand puppet. Rod puppet can be manipulated by a main-rod (connected to a puppet head) and two hand rods (connected to puppet’s hands), known as "three rods", and it is named as "rod" for its resemblance to old man’s walking stick. In China, the most representative rod puppet troupe is China National Puppet Arts Troupe2, in which Mr. Tan used to work.